Linking Circular Economy and Sustainable Energy Technology through Quintuple Helix Perspective - Waznatol Widad Mohamad Ishak; Siti Indati Mustapa; Norsyahida Mohammad; Azlina Mohamad Jais (Journal of Governance Risk Management Compliance and Sustainability, 2021)
Sustainable energy development had been signified as the pathways for the global energy transition, that drive important changes in how energy is being generated, transmitted, and consumed. The concept of Circular Economy (CE) has been proposed to address the environmental problem by minimizing the resource inputs and emission generation, reuse the waste and refuse from the conventional production process to obtain a further benefit. However, the contribution of CE to sustainable energy development and its link to Quintuple Helix (QH) elements is still ambiguous. This paper intends to fulfil this gap by examining the five main elements of the QH that contribute to the CE ecosystem, namely academia, companies, environment, government, and society. Innovative technologies from sludge management in urban wastewater sectors are discussed as the case study. A framework relating the QH with CE and innovation are proposed for future research. Practical recommendations associated with CE and sustainable energy policies are also provided.